Organizational Readiness to Change Assessment Highlights Differential Readiness for Antibiotic Stewardship. (October 2020) - Goebel, Melanie; Trautner, Barbara; Wang, Yiqun; Center, Affairs Medical; Van, John; Dillon, Laura; Center, Affairs Medical; Patel, Payal; Graber, Christopher; Helfrich, Christian; Grigoryan, Larissa
Abstract : Background: Targeted antibiotic stewardship interventions are needed to reduce unnecessary treatment of asymptomatic bacteriuria (ASB). Organizational readiness for change is a precursor to successful change implementation. The Organizational Readiness to Change Assessment (ORCA) is a validated survey instrument that has been used to detect potential obstacles and tailor interventions. In an outpatient stewardship study, primary care practices with high readiness to change trended toward greater improvements in antibiotic prescribing. We used the ORCA to assess barriers to change before implementing a multicenter inpatient stewardship intervention for ASB. Methods: Surveys were self-administered by healthcare professionals in inpatient medicine and long-term care units at 4 geographically diverse Veterans' Affairs facilities during January–December 2018. Participants included providers (physicians, physician assistants, and nurse practitioners), nurses, pharmacists, infection preventionists, and quality managers. The survey included 7 subscales: evidence (perceived evidence strength) and 6 context subscales (favorability of the organizational context to support change). Responses were scored on a 5-point Likert scale, with 1 meaning very weak or strongly disagree. Scores were compared between professional types and sites. We also measured allocated employee effort for stewardship at each site. Results: Overall, 104 surveys were completed, with an overall response rate of 69.3%. For all sites combined, the evidence subscale had the highest score of the 7 subscales (mean, 4; SD, 0.9); the resources subscale was significantly lower than other subscales (mean, 2.8; SD, 0.9; P < .001). Scores for budget and staffing resources were lower than scores for training and facility resources ( P < .001 for both comparisons). Pharmacists had lower scores than providers for the staff culture subscale ( P = .04). Comparing subscales between sites, ORCA scores were significantly different for leadership behavior (communication and management), measurement (goal setting and accountability), and general resources (Fig. 1). The site with the lowest scores for resources (mean, 2.4) also had lower scores for leadership behavior and measurement, and lower pharmacist effort devoted to antibiotic stewardship. Conclusions: Although healthcare professionals endorsed the evidence about nontreatment of ASB, perceived barriers to antibiotic stewardship included inadequate resources and lack of leadership support. These findings provide targets for tailoring the intervention to maximize the success of our stewardship program. Our support to sites with lower leadership scores includes training of local champions who are dedicated to supporting the intervention. For sites with low scores for resources, our targeted implementation strategies include analyzing local needs and avoiding increased workload for existing personnel. Funding: None Disclosures: None